A case-study evaluation of the “Copenhagen Music Program” for psilocybin-assisted therapy - Ratkovic, Gina; Sosteric, Mike; Sosteric, Tristan (Frontiers in Psychology, 2023)
In the journal Frontiers in Psychology, authors Messel et al. (2022, p. 1) provide a curated list, the “Copenhagen Music Program for Psilocybin” of music “tailored to the intensity profile of a medium/to high dose psilocybin” session. We test their music program with an experienced Indigenous therapist/psychonaut on a 3.5 gram psilocybin journey. Based on comments provided by the Indigenous therapist, we find the program contains musical choices that evoke specific colonial and religious contexts. We also find the program psychologically and emotionally coercive, meaning it is intended to force the individual on a specific experiential pathway. We conclude the program is not suitable for Indigenous travellers, question the author’s suggestion that travellers should be “encouraged” to stay with music they do not like, and suggest that curation of a wider variety of playlists, and music more in line with traditional shamanic practices might be a better approach to psychedelic curation.